#### Answer

$2x^3-13x^2+26x-15$

#### Work Step by Step

$(2x - 5)(x^2 - 4x + 3) $
$=2x^3-8x^2+6x-5x^2+20x-15$
$=2x^3-13x^2+26x-15$

Published by
Pearson

ISBN 10:
0-13446-914-3

ISBN 13:
978-0-13446-914-0

$2x^3-13x^2+26x-15$

$(2x - 5)(x^2 - 4x + 3) $
$=2x^3-8x^2+6x-5x^2+20x-15$
$=2x^3-13x^2+26x-15$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.